2016
DOI: 10.3389/fmicb.2016.00828
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-Acetic Acid Is Produced by Emiliania huxleyi Coccolith-Bearing Cells and Triggers a Physiological Response in Bald Cells

Abstract: Indole-3-acetic acid (IAA) is an auxin produced by terrestrial plants which influences development through a variety of cellular mechanisms, such as altering cell orientation, organ development, fertility, and cell elongation. IAA is also produced by bacterial pathogens and symbionts of plants and algae, allowing them to manipulate growth and development of their host. They do so by either producing excess exogenous IAA or hijacking the IAA biosynthesis pathway of their host. The endogenous production of IAA b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 104 publications
(153 reference statements)
5
62
0
Order By: Relevance
“…The results of our experiments indicate that all produced IAA is fully labeled (Figure 5b), thus indicating that exogenous tryptophan is directly converted to IAA. Of note, a recent study reported on the production of IAA in the mM range in axenic E. huxleyi cultures supplemented with tryptophan (Labeeuw et al, 2016). As all of our experiments and controls indicated no IAA production by algae, currently we do not understand the source of this apparent contradiction.
10.7554/eLife.17473.008Figure 5.Exogenous tryptophan promotes bacterial IAA biosynthesis.( a ) Addition of 0.1 mM tryptophan to P. inhibens cultures results in approximately 25-fold increase in produced IAA.
…”
Section: Resultsmentioning
confidence: 99%
“…The results of our experiments indicate that all produced IAA is fully labeled (Figure 5b), thus indicating that exogenous tryptophan is directly converted to IAA. Of note, a recent study reported on the production of IAA in the mM range in axenic E. huxleyi cultures supplemented with tryptophan (Labeeuw et al, 2016). As all of our experiments and controls indicated no IAA production by algae, currently we do not understand the source of this apparent contradiction.
10.7554/eLife.17473.008Figure 5.Exogenous tryptophan promotes bacterial IAA biosynthesis.( a ) Addition of 0.1 mM tryptophan to P. inhibens cultures results in approximately 25-fold increase in produced IAA.
…”
Section: Resultsmentioning
confidence: 99%
“…However, Segev et al (2016) also showed that P. inhibens did not produce IAA at high enough concentrations to kill E. huxleyi CCMP3266 (0.4-10 nM). In addition, E. huxleyi CCMP3266 produces IAA itself as a cell-cell signal at a higher concentration (200 µM) in the presence of tryptophan (Labeeuw et al, 2016). Finally, the Ntype strain, CCMP2090, is susceptible to IAA when co-cultured at lower concentrations (10-100 µM), exhibiting morphological responses and reduced health similar to those seen in terrestrial plants (Labeeuw et al, 2016) that we did not observe in the P. inhibens-CCMP2090 co-culture.…”
Section: Are Roseobacticides Responsible For Death Of C-and S-type Cementioning
confidence: 61%
“…Segev et al (2016) has proposed that P. inhibens uses IAA to kill E. huxleyi. This plant auxin is produced by various roseobacters (Fernandes et al, 2011;Wienhausen et al, 2017), including P. inhibens, and can kill the C-type culture, CCMP3266, at high concentrations (1,000 µM) (Labeeuw et al, 2016;Segev et al, 2016). However, Segev et al (2016) also showed that P. inhibens did not produce IAA at high enough concentrations to kill E. huxleyi CCMP3266 (0.4-10 nM).…”
Section: Are Roseobacticides Responsible For Death Of C-and S-type Cementioning
confidence: 99%
“…Algal biomass has the ability to grow under harsh conditions like saline, brackish water, which does not affect any conventional agriculture. 133 The disadvantage attached with the use of algal biomass as a feedstock is its higher cultivation cost as compared with conventional crops because of high energy input. Similarly, harvesting of algae requires high energy input, which is 20% to 30% of the total production cost.…”
Section: Algal Biomass For Biofuelmentioning
confidence: 99%